"Private" JPEG Images for Earth Science Purposes. Issue 1 (December 2020) - Carpentieri, Bruno
Abstract: The 5G era that is about to come will exponentially increase the amount of digital data produced. Already, the giant amount of digital data that is produced every day by sensors, users and digital devices has called for scalable and efficient decentralized approaches to data storage and elaboration and to a Fog/Edge computing paradigm that requires efficient networking and storage for better services related to the compression and security of digital data. In this paper, we will explore a unified approach that merges compression and security in one step, by reviewing the current research in this field and by presenting new experimental evidence and new ideas for secure compression of two-dimensional data (for instance digital images). The purpose of our study is also the masking and unmasking of the sensitive biometric data, i.e. face and eyes, that are contained within a JPEG image that contains human faces.